Chosen aspects of current psychological condition in relation to coping strategies of nurses in Slovakia - Pašková, Lucia (Central European Journal of Nursing and Midwifery, 2018)
Aim:To analyze chosen aspects of the current psychological state of Slovak nurses, and their relation to preferred strategies forworkload management. Design:Cross-sectional study. Methods:The research sample consisted of 240 nurses. Mikšík's SUPSO questionnaire was used in order to record and evaluate the structure and dynamics of subjective experiences and conditions. Stress management strategies were identified through Tobin's Coping Strategies Inventory (CSI) questionnaire, and the frequency of the experience of individual emotions through the SEHP Emotional Subjective Habitual Wellbeing questionnaire. The relationships between the variables were subjected to the Spearman correlation coefficient. Results:Nurses reported lower levels of psychological wellbeing and activity than the population average, as opposed to asthenic experience ofstress and uncertainty. Regarding preference of coping strategies in the context of work, nurses mainly use problem solving, social support, and cognitive restructuring. Regarding the mutual relationship of current psychological state and preferencesincoping strategies, there were significant positive relationships between a positively-attuned psychologicalstate and aninclination toward problem-oriented strategies, and, in terms of negative experiences, with divergent strategies. Conclusion:Recognizing the relationship between nurses' current psychological state and preferences in terms of coping strategies allows the application of adequate preventive programs, thereby improving the physical wellbeing of nurses and their ability to copewith the demands of the profession, with potentially positive outcomes in specific nursing activities.
Keywords: psychický stres; deprese; Stress, Psychological; Cross-Sectional Studies; kvalita života; Mental Health; zdravotní sestry; Quality of Life; Depression; duševní zdraví; průřezové studie; Nurses